Perbandingan pertumbuhan dan produksi kedelai edamame (Glycine max (L.) Merr.) pada berbagai dosis pupuk organik dan pupuk buatan - Anis Khaerunnisa; Arifah Rahayu; Sjarif Avitidjadi Adimihardja (Universitas Djuanda Bogor, 2015)
The study was aimed at assesing the effects of the aplication of organic and syntheticfertilizer on the growth and production of soybean. Four levels of organic fertilizer, namely noorganic fertilizer (0 ton ha -1), 0,5 x recomended rate (10 ton ha -1), 1 x recomended rate (20 ton ha -1) and 1,5 recomended rate (30 ton ha -1). The second factor was sinthetic fertilizer in fourlevels, namely no synthetic (0 ton ha -1), 0,5 x recomended rate (Urea 75 kg ha -1, SP-36 75 kg ha - 1, KCl 50 kg ha -1), 1 x recomended (Urea 150 kg ha -1, SP-36 150 kg ha -1, KCl 100 kg ha -1), and1,5 x recomende (Urea 225 kg ha -1, SP-36 225 kg ha -1, KCl 150 kg ha -1). Result show that theaplication of both organic and synthetic fertilizer gave significant effect on plant height, number of leaves, number of flowers, number of branches, leaf widht, number of total pods, number of pods containing 1, 2 and 3 seeds, fresh and dry weight of pods, fresh weight of roots, number of nodes,fresh weight of nodes, and fresh and dry weight of canopy. Interaction effect of organic andsynthetic fertilizer were found on dry weight of root, dry weight of nodes and dry weight ofbiomass.Keywords: edamame, organic fertilizer, synthetic fertilizer, pods